Use of the Delphy Technique: a case for the development of ecotourism in western Lombok - Rahmawati Rahmawati; Soenarto Soenarto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
Delphi technique was developed in 1950 by researchers at the Rand Corporation led by Norman Delkey and Olaf Helmer and has since been used in hundreds of businesses forecasting in the public and private sectors. Delphi technique is a judgmental forecasting procedure for obtaining, exchanging, and developing an informed opinion about future events. Therefore, the Delphi technique is a systematic way to get a consensus of opinion among the experts who have related interests through a panel discussion. The objective of most Delphi is the reliable and creative exploration of ideas or the production of suitable information for decision making. The key features of the Delphi technique, namely: (1) systematic, (2) questionnaire, (3) expert judgment, (4) iteration process, and (5) feedback. Baseline characteristics of the Delphi technique (conventional) there are five, namely: (1) anonymity, (2) iteration, (3) controlled feedback, (4) statistical group response, and (5) expert consensus. While the characteristics of a policy Delphi also five, namely: (1) selective anonymity, (2) informed multiple advocacies, (3) polarized statistical response, (4) structured conflict, and (5) computer conferencing. Steps in the application of policy Delphi there are seven, namely: (1) issue specification, (2) selection advocates, (3) questionnaire design, (4) analysis of first-round results, (5) development of subsequent questionnaires, (6) organization of group meetings, and (7) preparation of final report.